2004
DOI: 10.1212/01.wnl.0000130455.38550.9d
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative measurement of pain sensation in patients with Parkinson disease

Abstract: Endogenous pain in patients with Parkinson disease is accompanied by increased sensitivity to some painful stimuli, suggesting that basal ganglia abnormality also involves pain encoding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
183
10
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 265 publications
(223 citation statements)
references
References 46 publications
21
183
10
7
Order By: Relevance
“…It provides information on the level and underlying mechanism of pain of various etiologies. Studies of QST in patients with PD and primary central pain reported impaired pain processing, with lower heat pain thresholds than in patients with PD without pain (Djaldetti et al, 2004;Schestatsky et al, 2007). Heat pain thresholds were also lower in the more affected than the less affected hand (Djaldetti et al, 2004).…”
Section: Introductionmentioning
confidence: 95%
“…It provides information on the level and underlying mechanism of pain of various etiologies. Studies of QST in patients with PD and primary central pain reported impaired pain processing, with lower heat pain thresholds than in patients with PD without pain (Djaldetti et al, 2004;Schestatsky et al, 2007). Heat pain thresholds were also lower in the more affected than the less affected hand (Djaldetti et al, 2004).…”
Section: Introductionmentioning
confidence: 95%
“…Sensory symptoms (olfactory dysfunction, pain, paresthesia, akathisia, oral pain and genital pain) are frequent in PwP, but are often not recognised as parkinsonian symptoms [21,46,25,10].…”
Section: Motor Symptomsmentioning
confidence: 99%
“…The improvement of the pain was found in 59.26% of the patients under levodopa effect. However, in 40.7% of these patients this was not observed, suggesting that in addition to the patients who were in "wearing-off" status, there must have been nondopaminergic mechanisms related to primary pain in PD 14 . Recent studies had shown a reduction of the threshold to pain in PD 14,28 .…”
Section: Methodsmentioning
confidence: 88%
“…However, in 40.7% of these patients this was not observed, suggesting that in addition to the patients who were in "wearing-off" status, there must have been nondopaminergic mechanisms related to primary pain in PD 14 . Recent studies had shown a reduction of the threshold to pain in PD 14,28 . Brefel-Courbon et al 28 investigated the pain in PD patients and controls by means of thermal stimulation and cerebral activity with positron emission tomography.…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation